Sensor fusion of electronic nose and electronic tongue for classification of Orthosiphon stamineus - Zakaria, A.; Ali Yeon, Md Shakaff, Prof. Dr.; Adom, Abdul Hamid, Assoc. Prof. Dr.; Mohd Nor, Ahmad, Prof. Dr.; Shaari, A. R.; Jaafar, M. N., Prof. Madya. Dr.; Abdullah, A. H.; Fikri, N. A.; Latifah Munirah, Kamarudin (American Scientific Publishers, 2011)
Link to publisher's homepage at http://www.aspbs.com/